Transmission of Islamic Religious Education Values in the Religious Traditions of the Dayak Paser Muluy Community of Gunung Lumut, East Kalimantan - Rif'ah Rif'ah; Fahmi Hamdi; Salamah Salamah (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to analyze the transmission process of Islamic religious education values within the religious traditions of the Dayak Paser Muluy community in the Gunung Lumut area, East Kalimantan. This research is motivated by the interaction between Islamic teachings and local traditions that develop within indigenous communities, which forms distinctive and contextual religious practices. This study employs a qualitative approach using the library research method. The research data were obtained from various literature sources such as books, scientific journal articles, research reports, and other academic documents relevant to Islamic education studies, local culture, and Dayak indigenous communities. The data analysis technique used descriptive qualitative analysis by reviewing, interpreting, and synthesizing various literature sources to understand how the values of Islamic religious education are transmitted within the religious traditions of the Dayak Paser Muluy community. The results show that religious traditions in the Dayak Paser Muluy community serve as an important medium for transmitting Islamic educational values such as spirituality, solidarity, mutual cooperation, deliberation, respect for parents, and social care. These values are passed down through cultural practices, traditional rituals, social interactions, and the roles of traditional and religious leaders within the community. Local traditions function not only as a cultural identity but also as an informal educational medium that shapes the character and morality of the community in accordance with Islamic teachings. The novelty of this study lies in integrating the study of Islamic religious education with the perspective of local wisdom of the Dayak Paser Muluy community, thereby providing new insights into how local traditions function as a medium for transmitting Islamic educational values within indigenous societies.